2018
DOI: 10.1021/acs.cgd.7b01769
|View full text |Cite
|
Sign up to set email alerts
|

Threading Salen-type Cu- and Ni-Complexes into One-Dimensional Coordination Polymers: Solution versus Solid State and the Size Effect of the Alkali Metal Ion

Abstract: Compartmentalization of metal ions is crucial in biology as well as in materials science. For the synthesis of single source precursors, the preorganization of different metal ions is of particular interest for the lowtemperature generation of mixed metal oxides. On the basis of a potentially Ω-shaped salen-type ligand providing an N 2 O 2 as well as an O 2 O 2 coordination site, mixed metal coordination compounds with Cu(II) or Ni(II) and alkali metal ions have been studied for their structural and optical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 95 publications
(149 reference statements)
1
18
0
Order By: Relevance
“…[37][38][39] Salamo-like metal complexes have better flexibilities and selectivities, [40] nitrogen and oxygen atoms in N 2 O 2 cavity are easier to bind to different metal ions. [41][42][43] Of course, it can also be expected to obtain more novel metal complexes because of the different metal ions added. [44][45][46][47] The biological antimicrobial activities of oxime-type metal complexes have been widely studied, [31,32] however, salamo-like complexes are still lacking in this field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39] Salamo-like metal complexes have better flexibilities and selectivities, [40] nitrogen and oxygen atoms in N 2 O 2 cavity are easier to bind to different metal ions. [41][42][43] Of course, it can also be expected to obtain more novel metal complexes because of the different metal ions added. [44][45][46][47] The biological antimicrobial activities of oxime-type metal complexes have been widely studied, [31,32] however, salamo-like complexes are still lacking in this field.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that some salamo‐like metal complexes are much more stable than corresponding salen‐like metal complexes . Salamo‐like metal complexes have better flexibilities and selectivities, nitrogen and oxygen atoms in N 2 O 2 cavity are easier to bind to different metal ions . Of course, it can also be expected to obtain more novel metal complexes because of the different metal ions added .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, 71 we have explored the heterometallic systems derived from a 3-methylsalicylaldehyde-diamine ligand (H 2 L) containing two specific coordination sites. 72,73 Its central coordination site was composed of an imine-based N 2 O 2 entity coordinating either Cu(II) or Ni(II) ions.…”
Section: Introductionmentioning
confidence: 99%
“…They can coordinate with alkaline earth, rare earth, and d-block transition metal ions to form stable mononuclear or multinuclear metal coordination compounds [1][2][3][4][5]. It has been found that these salen-like complexes have various special structures and interesting properties [6][7][8]. In recent years, based on the research of salen and its derivatives, a new salamo-like ligand and its derivatives (R-CH=N-O-(CH 2 ) n -O-N=CH-R) have been developed, as the cavity formed by N 2 O 2 is easier to bind with metal ions [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%